Identification of the O/ME-SA/Ind-2001e Sublineage of Foot-and-Mouth Disease Virus in Cambodia - Ryoo, Soyoon; Lee, HyunJi; Lim, Da-Rae; Lee, Jung-Won; Bunnary, Seng; Tum, Sothyra; Lee, Dong Sook; Hwang, Hyeonwoo; Jeong, SomGyeol; Nah, JinJu; Ku, Bok Kyung; Kim, Jae-Myung; et al. (Frontiers in Veterinary Science, 2021)
Foot-and-mouth disease (FMD) has been reported to be endemic in Cambodia with numerous outbreaks in cattle, pigs, and other susceptible animal species. These outbreaks are caused by the FMD virus (FMDV) of serotype O PanAsia and Mya-98 lineages and serotype A Sea-97 lineage. However, the recent trans-pool movement of FMDV has raised concerns regarding infection with the new genotype or serotype of FMDV in this region. In this study, clinical samples (n = 33) originating from FMDV-affected cattle farms in Cambodia, in January through March, 2019 were genetically characterized to investigate the possible circulation of novel genotypes or serotypes. Phylogenetic analysis of VP1 sequences revealed that all recent field viruses belonged to O/ME-SA/Ind-2001e (15.8%), O/ME-SA/PanAsia (52.7%), and A/ASIA/Sea-97 (31.5%). Importantly, field viruses of the novel sublineage, O/ME-SA/Ind-2001e, were similar to strains that have caused recent outbreaks of FMD in India and Myanmar with 95.7–96.8% nucleotide sequence similarity. This is the first report of O/ME-SA/Ind-2001e infection in Cambodia, suggesting that the trans-pool movement of the new genotype should be closely monitored for efficient control of FMD.